Stature and Its Estimation Utilizing Arm Span Measurements of both gender Adolescents from Ferizaj Region in Kosovo - Hazir Salihu; Afrim Koca; Florian Miftari; Fitim Arifi (Kazimierz Wielki University, 2018)
This study is based on measurements of Ferizaj region Kosovan adolescents. The aim of this study was to examine the stature of adolescents from Ferizaj region as well relationship between arm span and stature in both genders. A total measured subject participated in this research was 174 out of which (79 girls and 95 boys), females average of age is 18.36±0.50 years old (range 18-20 years) and for male 18.40±0.55 years old (range 18-20 years).The anthropometric measurements were done by trained people and were taken according to the ISAK manual. Relationship between stature and arm span has been analyzed by the simple correlation coefficient at a 95% confidence interval. The linear regression analysis was carried out to examine extent to which arm span can reliably predict of stature. Statistical importance was placed at level p